104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
Howard Watkins receiving plaque from Judy Soley; Herbert Levy, William J. Smith, Dana French, Mary Louise Frampton and Howard Zidenberg at head table